A Content Analysis of Polemics in a Regulation Regarding Sexual Violence on Campus - Rona Rizkhy Bunga Chasana; Putri, Devi Afriyantari Puspa; Vernanda, Yuniar (Mediator: Jurnal Komunikasi, 2023)
The government hopes that the release of the Minister of Education and Culture Regulation concerning the Prevention and Handling of Sexual Violence (Permendikbudristek PPKS) No. 30 of 2021 can address the problem of sexual violence on campus. However, this regulation sparked debate among various parties who disagreed with the phrase "without the victim's consent" contained in several articles. Various public opinions on social media and news, both pros and cons, have emerged in various online media. Media coverage of crisis issues can exacerbate the crisis in an organization. This study aims to assess the use of news frames in online news media. A total of 35 articles from Republika.co.id and Kompas.com were analyzed. Using quantitative content analysis, this research was conducted by exploring 5 media frames that commonly appear in crisis-related news: attributions of responsibility, conflict, economic consequences, morality, and human interests. The result is that the conflict frame is the most dominant frame followed by the responsibility frame. Meanwhile, morality and human interests are the least used frames. Studying crisis news frames is important for PR practitioners to understand media coverage during a crisis and provide appropriate responses to mitigate its impact.